Antitumoral Action of Resveratrol Through Adenosinergic Signaling in C6 Glioma Cells - Sánchez-Melgar, Alejandro; Muñoz-López, Sonia; Albasanz, José Luis; Martín, Mairena (Frontiers in Neuroscience, 2021)
Gliomas are the most common and aggressive primary tumors in the central nervous system. The nucleoside adenosine is considered to be one major constituent within the tumor microenvironment. The adenosine level mainly depends on two enzymatic activities: 5′-nucleotidase (5′NT or CD73) that synthesizes adenosine from AMP, and adenosine deaminase (ADA) that converts adenosine into inosine. Adenosine activates specific G-protein coupled receptors named A1, A2A, A2B, and A3 receptors. Resveratrol, a natural polyphenol present in grapes, peanuts, and berries, shows several healthy effects, including protection against cardiovascular, endocrine, and neurodegenerative diseases and cancer. However, the molecular mechanisms of resveratrol actions are not well known. Recently, we demonstrated that resveratrol acts as an agonist for adenosine receptors in rat C6 glioma cells. The present work aimed to investigate the involvement of adenosine metabolism and adenosine receptors in the molecular mechanisms underlying the antitumoral action of resveratrol. Results presented herein show that resveratrol was able to decrease cell numbers and viability and to reduce CD73 and ADA activities, leading to the increase of extracellular adenosine levels. Some resveratrol effects were reduced by the blockade of A1 or A3 receptors by DPCPX or MRS1220, respectively. These results suggest that reduced CD73 activity located in the plasma membrane in addition to a fine-tuned modulatory role of adenosine receptors could be involved, at least in part, in the antiproliferative action of resveratrol in C6 glioma cells.